Flexural and compressive behaviour of composite concrete with 0.5% of polyester / Muhamad Alpiza Che Ibrahim (Faculty of Civil Engineering, 2003)
Plain, unreinforced cementitious composites in general and concrete in particular, had low tensile strengths and low tensile strain capacities. The tensile strain capacity of cement from cement-based materials can be improved by the addition of fiber. In addition, the performance of the concrete can be improved by replacing some percentage of cement with silica fume. Research shown that silica fume could be used as a substitute for cement to reduce the cost of concrete products, as an admixture to improve the quality of concrete, and as a concrete making materials to produce concrete products and structures with high performance (Kawamura, M., 1992). This study presents the investigation experimentally the performance of polyester fiber and silica fume in grade 60 concrete. Tests had been carried out on concrete with 0.5% of polyester fiber with 12% and 16% of silica fume (SF). The properties of concrete that had been investigated include the workability using the Slump Test and Vebe Test then the strength of concrete using Compressive Strength and Flexural Strength Tests. The results of these tests then had been compared with concrete of 0% fiber as control specimen. Compressive test had been carried out on a total of 120 concrete cubes samples with dimension of 150mm x 150mm x 150mm. Four point bending test had been carried out on a total of 12 prisms samples with dimension of 100mm x 100mm x 500mm, and fracture toughness determined at 28 days of age. As a result, sample with 12% SF is more workable than sample of 16% SF while sample with 16% SF gives 2.1% higher compressive strength than 12% SF. However, both of the samples give almost same result of the flexural strength that is 6.3 N/mm2.